Workplace learning in midwifery education in Flanders (Belgium). (February 2016) - Embo, M.; Valcke, M.
Abstract: Workplace learning plays a crucial role in midwifery education. Twelve midwifery schools in Flanders (Belgium) implemented a new competency framework and aimed at implementing a more standardized and evidence-based method to learn and assess competencies, as well as to guide continuous competency development in practice. This paper describes the introduction of 'Embo's continuous workplace learning model', a holistic and competency-based method that integrates all workplace learning components. Available research evidence helps concluding the learning model is a feasible approach to organize workplace learning in such a way that continuous professional competency development is achieved.